Implementasi Bimbingan Kelompok Untuk Meningkatkan Hubungan Sosial Antar Teman Sebaya Di Kelas X.F SMA Negeri 2 Mengwi Tahun 2025. - Ega Dwi Meriani; Wayan Suastini (Universitas Muria Kudus, 2025)
This study was conducted based on classroom phenomena reported by several teachers and supported by data from the supervising teacher, indicating that students struggle with effective communication. Social isolation, which causes students to feel lonely, and negative judgments about individuals or groups based on false assumptions can hinder positive interactions.In response to this issue, the researcher implemented Group Guidance services to improve social relationships among peers in Class X.F at SMA Negeri 2 Mengwi in 2025. This service was provided to 30 students in Class X.F using PTBK data analysis techniques and a quantitative research method. The study concluded that the implementation of Group Guidance effectively enhances social relationships among peers in Class X.F at SMA Negeri 2 Mengwi in 2025. The group dynamics in the guidance sessions help students develop motivation, which influences peer interactions and fosters positive relationships among them.